Diagnosis and treatment of hemophagocytic histiocytic sarcoma in a cat. Issue 2 (October 2020) - Huber, Brian; Leleonnec, Marc
Case summary: A 7-year-old spayed female domestic shorthair cat was presented for persistent anemia of unknown origin. Splenomegaly was diagnosed through physical examination and abdominal radiographs, and an abdominal ultrasound was performed. The ultrasound showed splenomegaly, as well as one discrete mass in the body of the spleen. A splenectomy was performed and histopathology along with immunohistochemistry for CD18 and CD204 confirmed a diagnosis of hemophagocytic histiocytic sarcoma (HS). Two courses of lomustine (CCNU) chemotherapy were used in this cat along with adjuvant oral prednisolone and iron dextran injections, but the cat eventually succumbed to hepatic failure, presumed to be secondary to metastatic disease. Relevance and novel information: The clinical pathology results and ultrasonographic studies performed before and after treatment in this cat provide useful preliminary information about the biologic behavior and response to treatment for this rare cancer. This is also the first reported case where both CD18 and CD204 were strongly positive, confirming hemophagocytic HS in a cat.